Regional price levels in Germany - Michael W.M. Roos (European Regional Science Association (ERSA), 2003)
Cross-sectional evidence on price levels is scarce in all countries. However, several studies suggest that considerable differences in price levels within countries exist, which has obvious welfare implications. I use a sample of price levels in 50 German cities in 1993 to analyze the determinants of inter-city price level differentials. The most important factors driving price level differentials are population size and the average wage level. Using this information, I predict the price levels in all 440 German districts and aggregate them to the state level. On the state level I find convergence of the price levels to a common mean, but at a very low speed. The estimated half-life is about 15 years.
Keywords: 330